Sociology : understanding and changing the social world - Barkan, Steven E., 1951-; Saylor Foundation; BC Open Textbook Project; BCcampus (Saylor Foundation, 2014)
"The book includes the most recent data in the following categories, so your students have access to the latest sociological trends: crime and victimization, income and poverty, life expectancy and aging, employment, marriage and divorce, education, medical care and health disparities, and fertility and population change."--BCcampus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
Title from BC Campus Website.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on version viewed on BCcampus OpenEd website; title from pdf title page (viewed September 11, 2014).
Keywords: Sociology -- Textbooks; Electronic books